Development of Computerized Testlet to Measure Science Process Skill on Stoichiometry - Stefanus Kristiyanto; Ashadi Ashadi; Sri Yamtinah; Sri Mulyani (JKPK (Jurnal Kimia dan Pendidikan Kimia), 2019)
This research aims to develop a computerized testlet assessment to measure science process skills on stoichiometry material in terms of validity, reliability, difficulty level, distinguishing features and deception indexes that meet the criteria as good assessment instruments, and can display individual profiles of science process skills students. The subject of the research trial was a grade X student of Senior High School in Boyolali. Validity test is done by content validity, criteria, and expert validation. Reliability test is done by finding the price of the reliability coefficient r. Characteristics test is done by determining the level of difficulty, distinguishing features and deception index. The profile of science process skills is determined by measuring students' mastery of the science process. The results of the research and development was declared feasible and met the criteria as a good question with a validity of questions more than 0.79 (valid), has a test reliability on the main field trials of 0.643 and 0.610 on the trial the implementation of the field is relatively high, has a distinguishing power with a percentage of 10% bad, 66.7% is sufficient, and 23.3% is good, has a difficulty level with a percentage of 20% difficult, 53.3% moderate and 26.7% easy.